Calibrating Time Domain Reflectometers for Soil Moisture Measurements in Sandy Soils - Tara Bongiovanni; Pang-We Liu; Daniel Preston; Stevben Feagle; Jasmeet Judge (EDIS, 2017)
The UF/IFAS Plant Science Research and Education Unit (PSREU) in Citra, FL developed an in-laboratory calibration protocol for CS616 TDR sensors for sandy soils, which are typical of north central Florida. This new 7-page fact sheet discusses the reflectometer, field site, calibration protocol, and calibration coefficients. Written by Tara Bongiovanni, Pang-Wei Liu, Daniel Preston, Johanna Montanez, Courtnay Cardozo, Steven Feagle, and Jasmeet Judge, and published by the UF Department of Agricultural and Biological Engineering, February 2017. http://edis.ifas.ufl.edu/ae519